Analisis Ability to Pay dan Willingness to Pay Penggunaan Parkir di Pasar Banjaran Kabupaten Tegal - Sulfah Anjarwati; Juanita Juanita (Proceedings Series on Physical & Formal Sciences, 2021)
The problem of setting tariffs is often a point of conflict between communities and managers. On the one hand, the community wants tariffs at the lowest level according to their capabilities with satisfactory service, on the other hand, the management wants high rates that can generate satisfactory profits. Basically, the determination of parking rates in accordance with the ability and willingness of the community will make it easier for users of parking facilities to pay the tariffs, especially if balanced with adequate services and facilities. Formulate the problem in this study is how the ability and willingness to pay parking users in the Banjaran Market area and whether the existing parking rates are in accordance with the ability and willingness of parking users in the Banjaran Market?. The method used in this study is descriptive analysis method, descriptive is a systematic, actual and accurate depiction of facts, data on events being studied. Analysis is the arrangement of data to obtain answers to questions that arise in research. For users of parking facilities for two-wheeled and four-wheeled vehicles on weekdays, the ATP value is obtained. The first hour tariff is Rp. 1,629.39, the progressive parking rate is Rp. 629, 39 WTP the tariff is Rp. Rp 1.388.08. For users of two-wheeled and four-wheeled vehicles on weekends, the ATP value for the first hour is Rp. Rp. 1,388.08 and the next hour tariff is Rp. 388.08 with a fixed WTP rate of Rp. 1388.08. From all calculations ATP is greater than WTP. The difference between the amount of ATP and WTP from the results of the analysis can occur due to several factors, one of which is the large percentage of parking fee allocation used as a component of ATP calculations that is not suitable for the tariffs applied at the Banjaran Market.